An Atlas and Survey of South Asian History - Schmidt, Karl J., 1963- (Armonk M.E. Sharpe, 1995)
This historical atlas is devoted primarily to India, Bangladesh and Pakistan, while also covering Napal, Bhutan and Ceylon/Sri Lanka. The maps are accompanied by text which illuminates recent political, economic, social and cultural developments.
Include Map, Glossary and Index
Keywords: South Asia -- Historical geography